Analisis Faktor Yang Berhubungan Dengan Pemberian Kolostrum Pada Hari Pertama Kelahiran - Indrie Lutfiana; Kadek Agustina Puspa Ningrum (PT Nuansa Fajar Cemerlang, 2026)
Background: Nutrition provided through Breast Milk (ASI) has substantial implications for the quality of a child's development. An observation conducted in the Postpartum Room indicated that some breastfeeding mothers do not provide colostrum to their babies. This occurs quite frequently, with factors such as knowledge, education, and family support being among the reasons for not providing colostrum. Method: This study adopts a quantitative paradigm through the design of an analytical survey with a cross-sectional design. The participants of this study included 250 postpartum mothers, with 80 mothers sampled using purposive sampling technique. The research location was in the postpartum ward the period of March 2026. The research instrument consisted of a questionnaire that collected participant demographic data, knowledge level, family support, and educational history. Univariate analysis focused on frequency distribution, while bivariate analysis applied the Spearman-rank test. Results: Of the 80 participants studied, the majority of respondents showed an adequate level of knowledge, comprising 66 mothers (82.5%), those with a high school education background numbering 66 mothers (82.5%), and family support assessed as sufficient by 50 mothers (62.5%). Statistical analysis using the Spearman-rank method yielded a p-value of 0.001, which is significantly lower than the established threshold (< 0.05), thus the alternative hypothesis (Ha) is accepted. This finding indicates a correlation between the knowledge level of breastfeeding mothers and the practice of colostrum feeding on the first day of birth in the postpartum room. Conclusion: There is a significant correlation between the knowledge level of breastfeeding mothers and the practice of colostrum administration on the first day of birth in the postpartum room. It is expected that health workers regularly provide education and counseling to breastfeeding mothers to improve colostrum administration on the first day of birth